Se ressaisir - Rose-Marie Lagrave (Genre, Sexualité et Société)
It was in the process of looking back on an indescribable family life that had been impossible to classify, and also through the encounter of a schoolteacher that had found his calling as an instructor – both indelibly leaving their marks on her path in life – that the author identified herself as a class defector. From then on when questioned from a perspective of gender, that category was in effect heterogeneous. By indentifying how the role of feminine engagements, (both social and academic) has gone through multiple bifurcations, the author demonstrates that feminism appropriates its own politicized methodology of being and of envisioning the world.